Modeling of (GaP)m/(AlP)n superlattices using empirical tight-binding method. (January 2021) - Ebrahim Zargar, Ali Haji; Yazdanpanah, Vahid Reza; Ayatollahi, Ahmad
Abstract: In this paper, we investigated behavior of energy gap and refractive index of (GaP)m /(AlP)n superlattices structure (SLS) grown on GaP (100) substrate in terms of GaP and AlP thicknesses. For this purpose, we used the empirical tight-binding method (ETBM) with sp 3 s* approximation and considering first nearest neighbor and spin-orbit interactions. Since in this method, predicting 15 parameters in individual balk Hamiltonian matrix is very important, we used genetic algorithm to obtain a new set of parameters that can accurately predict the superlattice structures energy gaps with about 1.2% deviation from the experimental data points. We used these parameters and also considered stress, strain and energy band lineups for this SLS to simulate the energy gap and refractive index for a range of GaP and AlP thicknesses. Highlights: Introduction of new orbitals interaction parameters for GaP/AlP by using genetic algorithm, which help to have better description in bulk and superlattices. We compared the result of simulation by experimental values and results with other method and other orbitals interaction parameters. Prediction of GaP/AlP superlattice bandgap energy and refractive index by varying the thicknesses of both AlP and GaP and extracting a range of bandgap variations.